Comparison of Functional Outcome of Proximal Femoral Nail (PFN) and Dynamic Hip Screw (DHS) in Intertrochanteric Fractures of Femur under Spinal Anesthesia (Medical Forum Monthly, 2020)
Objective: To evaluate and compare the post-operative functional outcome of patients of intertrochanteric fractures of femur undergoing either dynamic hip screw (DHS)or proximal femoral nail (PFN) fixation presenting under spinal anesthesia in tertiary care hospital.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the Department of orthopedic, Unit I and Department of Anesthesia Mohi-ud-Din Teaching Hospital Mirpur AJK from March 2016 to April 2017.Materials and Methods: One hundred and fifty male and female patients fulfilling inclusion criteria presenting in orthopedic department. Their bio-data was recorded followed by an objective assessment of the intertrochanteric fracture of femur. Seventy-five patients underwent fixation with proximal femoral nail and 75 patients underwent fixation with dynamic hip screw by lottery method. Patients were objectively assessed first at 2 weeks post-operatively and then at 4 weekly intervals for up to 24 weeks for functional outcome in terms of Kyle’s criteria for good to excellent results.Results: Mean age of patients in dynamic hip screw group and proximal femoral nail group was 61.29±11.94 and 59.10±13.61 years respectively. In Group A, 25(33.34%) patients mode of injury was trauma due to road traffic accident and 50(66.64%) patients mode of injury was fall at home whereas in Group B 28(37.34%) patients had trauma due to road traffic accidents and 47(62.66%) were injured due to fall. Functional outcome was assessed by using Kyle’s criteria. At 8th, 12th, 20thand 24th week good to excellent functional outcome was significantly high in Group B as compared to Group A patients. (8th week: 26.67% vs. 44%, 12th Week: 36% vs. 52%, 20th Week: 85.33% vs. 100%, 24th Week: 92% vs. 98.66%) while at 16th week functional outcome was although high in Group-B patients but it was not statistically significant. (16th Week: 81.34% vs. 89.34).Conclusion: Proximal femoral nail is far better implant in terms of post-operative functional outcome as compared to dynamic hip screw for treating intertrochanteric femoral fractures. i.e. (Kyle’s Criteria at 24th Week: DHS: 92% vs. PFN: 98.66%).